2008
DOI: 10.1007/s00535-008-2174-9
|View full text |Cite
|
Sign up to set email alerts
|

Adding interferon to lamivudine enhances the early virologic response and reversion of the precore mutation in difficult-to-treat HBV infection

Abstract: Simultaneous commencement of treatment with interferon and a nucleoside analog may be worthy as a treatment option to augment the early virologic response and prevent drug resistance in difficult-to-treat patients. Combination treatment was also shown to enhance reversion of the precore mutation. Further studies are warranted to clarify the therapeutic implications of this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Our results are compatible with these findings. Also, it has been reported that during the course of antiviral therapy, reversions from PC/BCP mutants to wild type HBV may occur (21, 22). In summary, in the current study, there is a relationship between mutation in the precore region and high viral load, which can involve in severity of liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are compatible with these findings. Also, it has been reported that during the course of antiviral therapy, reversions from PC/BCP mutants to wild type HBV may occur (21, 22). In summary, in the current study, there is a relationship between mutation in the precore region and high viral load, which can involve in severity of liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Antigen was only rarely visualized in bronchiolar epithelium and was not found in VOL. 83,2009 INFLUENZA VIRUS PATHOGENESIS IN GUINEA PIGS 2857 alveolar cells. This lack of virus antigen, along with moderate lung titers and the focal lung pathology among H5N1 and 1918 virus-infected guinea pigs, suggests that sites of virus replication are more restricted in the guinea pig lung than in other animal models.…”
Section: Discussionmentioning
confidence: 99%
“…In one report, combination of interferon-α with LMV for 24 weeks followed by LMV alone for 28 weeks resulted in 90% complete virologic response rate at week 8, compared with 33% in the LMV monotherapy group. At week 52, YMDD mutants were detected in 8% of patients on combination therapy versus 30% on the monotherapy [44]. In another study, interferon was used to reduce the viral load to less than 10 3 copies/mL; LMV was then added for 1 month, and continued as monotherapy for 24 months.…”
Section: Prevention Of Drug Resistancementioning
confidence: 97%